Course of Ocular Function in PRPF31 Retinitis Pigmentosa. (3rd March 2016) - Hafler, Brian P.; Comander, Jason; Weigel DiFranco, Carol; Place, Emily M.; Pierce, Eric A.
ABSTRACT: Mutations in pre-mRNA splicing factors are the second most common cause of autosomal dominant retinitis pigmentosa, and a major cause of vision loss. The development of gene augmentation therapy for disease caused by mutations in PRPF31 necessitates defining pretreatment characteristics and disease progression of patients with PRPF31 -related retinitis pigmentosa. We show rates of decline of visual field area −6.9% per year and 30-Hz flicker cone response of −9.2% per year, which are both similar to observed rates for retinitis pigmentosa. We hypothesize that RNA splicing factor retinitis pigmentosa will be amenable to treatment by AAV-mediated gene therapy, and that understanding the clinical progression rates of PRPF31 retinitis pigmentosa will help with the design of gene therapy clinical trials.